2014
DOI: 10.1021/es405234p
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plant Pb Tolerance at Realistic Submicromolar Concentrations Demonstrates the Role of Phytochelatin Synthesis for Pb Detoxification

Abstract: Lead (Pb) ranks first among metals with respect to tonnage produced and released into the environment. It is highly toxic and therefore an important pollutant of worldwide concern. Plant Pb uptake, accumulation, and detoxification mobilize Pb into food webs. Still, knowledge about the underlying mechanisms is very limited. This is largely due to serious experimental challenges with respect to Pb availability. In most studies, Pb(II) concentrations in the millimolar range have been used even though the toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 53 publications
1
43
0
1
Order By: Relevance
“…The transpeptidase activity results in the synthesis of PCs with varying chain lengths. PCs buffer labile cytosolic metal pools and thereby confer tolerance towards an excess of essential micronutrients such as Zn and non-essential metals/metalloids such as Cd, Pb or As (Cobbett & Goldsbrough 2002;Clemens & Persoh 2009;Fischer et al 2014). In order to test whether this latter activity is also underlying the immunity function of AtPCS1, we expressed a phylogenetically distant PCS in the cad1-3 mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transpeptidase activity results in the synthesis of PCs with varying chain lengths. PCs buffer labile cytosolic metal pools and thereby confer tolerance towards an excess of essential micronutrients such as Zn and non-essential metals/metalloids such as Cd, Pb or As (Cobbett & Goldsbrough 2002;Clemens & Persoh 2009;Fischer et al 2014). In order to test whether this latter activity is also underlying the immunity function of AtPCS1, we expressed a phylogenetically distant PCS in the cad1-3 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of plants exposed to toxic concentrations of the non-essential metals Cd, Hg and Pb or the metalloid As depends on the synthesis of phytochelatins (PCs), glutathione-derived peptides of the general structure (γ-Glu-Cys)n-Gly (Rea 2012;Fischer et al 2014). Their non-ribosomal synthesis is catalysed by PC synthases (PCS).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike cereals, legumes have unique ability to synthesize homo phytochelatins (hPCs) and homo glutathione (hGSH) in addition to PCs and GSH, respectively . It has been well documented that hPCs are formed in the legume plants or cell suspension cultures when they were placed with several metals and metalloids . Gupta et al observed that PCs and hPC were accumulated in Cicer arietinum L. on mixing with As(V) or Cd but not with Zn or Cu.…”
Section: Potentially Toxic Elements In Cereals and Legumesmentioning
confidence: 99%
“…For example, Arabidopsis thaliana mutants lacking the tonoplast-localized transporter MTP1 are Zn hypersensitive (Desbrosses-Fonrouge et al, 2005;Kawachi et al, 2009). Mutants with a defect in the synthesis of phytochelatins or the vacuolar sequestration of phytochelatins-metal complexes are hypersensitive to Zn, Cd, Pb, and As (Cobbett & Goldsbrough, 2002;Fischer, Kühnlenz, Thieme, Schmidt, & Clemens, 2014). Metal-rich habitats, however, may have levels of bioavailable metals that exceed the capacity of basal metal tolerance and can thus barely be colonized by the large majority of plant species.…”
mentioning
confidence: 99%